Augmented Reality to Enhance Informatics Learning Outcomes: A Quasi-Experimental Study in Vocational Education - Silvani Ilhani Fahira; Ika Parma Dewi; Ahmad Samed Al-Adwan; Richelle C. Castro (Sagamedia Teknologi Nusantara, 2025)
This study examines the effect of Augmented Reality (AR)-based learning media on Informatics learning outcomes at SMK Negeri 1 Bukittinggi, a vocational school recognized as a Centre of Excellence. Using a quasi-experimental pretest-posttest control group design, the study involved 70 tenth-grade students, divided into an experimental group (receiving AR-based learning media) and a control group (receiving traditional methods). The AR-based learning media focused on abstract Informatics concepts, such as algorithms and computer hardware, through interactive and immersive experiences. Results showed a significant improvement in the experimental group, with a mean post-test score difference of 7.31 points (p < 0.001). Statistical tests confirmed that the data met the assumptions of normality and homogeneity. Grounded in the cognitive theory of multimedia learning, the study highlights AR’s potential to enhance engagement, comprehension, and knowledge retention by integrating theoretical and practical knowledge. Despite limitations, such as a focus on cognitive outcomes and reliance on technological infrastructure, the research highlights AR’s transformative role in vocational education. Future studies should explore AR’s scalability in under-resourced settings, its long-term effects, and its applicability across several disciplines.